?EFFECT OF DIFFERENT CONCENTRATION OF KCION CONTRACTION PERFORMANCE OF GASTROCNEMIUS MUSCLE OF UROMASTIX HARDWICKII - Yaqeen, Zahra; nuddin, Yaqee; Mirzar, Maryam; Badar, Yasmeen; Shaikh, Hilal A (Biological Sciences - PJSIR, 1999)
This paperdealswithchangesinmuscularactivityoCgastrocnemiusmuscleof Uromastix liardwickii Correptilianbuffer havingdifferentconcentrationofKCI.Contractiontime,half relaxationlime,peakdurationtime,maximumrateof rise01" tensionandisotonictensionhavebeenselectedastheparametersforevaluationofmusclecontractionperformance.These studiesconfirmthat,maintenanceofK iontothenormalvaluebothintheextraandintracellularl1uidisnecessary,because itsdecreaseandincreasefrom thenormalvalueisdangerousforlife.